1998
DOI: 10.1111/j.1439-0434.1998.tb04678.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Calcium in Mediating Smut Disease Severity and Salt Tolerance in Corn under Chloride and Sulphate Salinity

Abstract: The effect of sahne irrigation water containing NaCl or Na2SO4 with and without CaSO4 application on the gram yield, smut index and plant nutrient contents of two intermediate smut-susceptible corn cultivars was investigated in cemented plots containing sandy loam soil. The plants were artificially infected and the disease severity was rated. At the end of silking stage, the leaf Cl, Na and Ca contents were detected and Ca/Na ratio was calculated. At harvest, the grain yield of smut-free and smutted plants was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Calcium is another interesting nutrient in relation to silks. Calcium improves grain yield and improves resistance of maize to Corn Smut under saline conditions [102]. When pollen hydration and germination occur, calcium ion (Ca 2+ ) levels in the silk trichomes (hairs) increase in a matter of seconds, and an electrical signal is propagated to the ovule [103].…”
Section: Strategies To Protect Silks From Ear Rot Pathogens—currenmentioning
confidence: 99%
“…Calcium is another interesting nutrient in relation to silks. Calcium improves grain yield and improves resistance of maize to Corn Smut under saline conditions [102]. When pollen hydration and germination occur, calcium ion (Ca 2+ ) levels in the silk trichomes (hairs) increase in a matter of seconds, and an electrical signal is propagated to the ovule [103].…”
Section: Strategies To Protect Silks From Ear Rot Pathogens—currenmentioning
confidence: 99%
“…With salinity level at the same electrolyte concentration, SO 4 2caused more injuries than Clin barley (Hordeum vulgare L.) (Datta et al, 1994(Datta et al, , 1995 while Clsuppressed the growth more than SO 4 2in wheat (Triticum aestivum L.) (Zahoor et al, 2007), rice (Oryza sativa L.) (Minhas et al, 2007), and corn (Zea mays L.) (Kostandi and Soliman, 1998). With salinity level at the same electrolyte concentration, SO 4 2caused more injuries than Clin barley (Hordeum vulgare L.) (Datta et al, 1994(Datta et al, , 1995 while Clsuppressed the growth more than SO 4 2in wheat (Triticum aestivum L.) (Zahoor et al, 2007), rice (Oryza sativa L.) (Minhas et al, 2007), and corn (Zea mays L.) (Kostandi and Soliman, 1998).…”
mentioning
confidence: 99%
“…Different effects by SO 4 2and Clhave been reported in various crops. With salinity level at the same electrolyte concentration, SO 4 2caused more injuries than Clin barley (Hordeum vulgare L.) (Datta et al, 1994(Datta et al, , 1995 while Clsuppressed the growth more than SO 4 2in wheat (Triticum aestivum L.) (Zahoor et al, 2007), rice (Oryza sativa L.) (Minhas et al, 2007), and corn (Zea mays L.) (Kostandi and Soliman, 1998). At same molar concentration, different salts may vary in osmotic potential, electrical conductivity (EC), and pH.…”
mentioning
confidence: 99%
“…El-Mougy and Abdel Kader (2009) reported that sodium bicarbonate or calcium chloride significantly reduced the early blight incidence and severity of tomato plants in pot experiments under artificial infestation with pathogenic fungus. Kostandi and Soliman (1998) stated that the effect of saline irrigation containing NaCl or Na 2 SO 4 reduced the smut occurrence by 22.7% & 10.8% respectively. The salinity resulted in soil suppressiveness to F. oxysporum a fungal agent of vascular wilt disease through reduced germination of conidia and mycelial growth (Amir et.al., 1996).…”
Section: Evaluation Of Salts On the Mycelial Growth Ofmentioning
confidence: 99%